Do adult mental health services identify child abuse and neglect? A systematic review. (17th August 2017) - Read, John; Harper, David; Tucker, Ian; Kennedy, Angela
Abstract: Child abuse and neglect play a causal role in many mental health problems. Knowing whether users of mental health services were abused or neglected as children could be considered essential for developing comprehensive formulations and effective treatment plans. In the present study we report the findings of a systematic review, using independent searches of three databases designed to discover how often mental health staff find out whether their clients were abused or neglected as children. Twenty‐one relevant studies were identified. Most people who use mental health services are never asked about child abuse or neglect. The majority of cases of child abuse or neglect are not identified by mental health services. Only 28% of abuse or neglect cases identified by researchers are found in the clients' files: emotional abuse, 44%; physical abuse, 33%; sexual abuse, 30%; emotional neglect, 17%; and physical neglect, 10%. Between 0% and 22% of mental health service users report being asked about child abuse. Men and people diagnosed with psychotic disorders are asked less than other people. Male staff ask less often than female staff. Some improvement over time was found. Policies compelling routine enquiry, training, and trauma‐informed services are required.